(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article, the analysis of the famous Uzbek poet and writer Ikrom Otamurad, his life and work, works, poems and epics Analysis was illuminated and analyzed on the basis of various approaches.